Evolution of Copper Nanospecies in the Synthesis Stages of MCM-41-Type Mesoporous Molecular Sieves - Chanquia, Corina Mercedes (2012)
The redox behavior of copper nanospecies in the synthesis stages of MCM-41-type materials has been followed by ESR technique. These coppermodified mesoporous molecular sieves (Cu-MMS) were synthesized by direct incorporation method, and different treatments of the initial synthesis gel were evaluated. From ESR and UVVis-DRS data, a synergistic approach about the distribution of copper species in the different catalysts has been made: the hydrothermal treatment favors the incorporation of isolated cooper species into the framework, whereas both the aging treatment and the lack of subsequent treatment promote the formation of copper clusters into the mesoporous channels. The Hamiltonian parameters g// = 2.3 and g = 2.06 have confirmed the presence of isolated Cu2+ ions in octahedral coordination with tetragonal distortion within siliceous framework, whereas the g = 2.2 value was assigned to the presence of Cu2+ clusters. Only the catalyst aged at room temperature has presented additional signals characteristic of Cu2+ dimers. Finally, it is found that during the template removal process at 773 K the so-called self-reduction phenomenon of isolated cupric ions takes place: a 50-70% decrease in the ESR signal intensity was observed for the final Cu-MMS.